The demand for cigarettes as derived from the demand for weight control - John H. Cawley; Stephanie von Hinke Kessler Scholder (Institute for the Study of Labor (IZA), 2013)
We provide new evidence on the extent to which the demand for cigarettes is derived from the demand for weight control (i.e. weight loss or avoidance of weight gain). We utilize nationally representative data that provide the most direct evidence to date on this question: individuals are directly asked whether they smoke to control their weight. We find that, among teenagers who smoke frequently, 46% of girls and 30% of boys are smoking in part to control their weight. This practice is significantly more common among youths who describe themselves as too fat than those who describe themselves as about the right weight. The derived demand for cigarettes has important implications for tax policy. Under reasonable assumptions, the demand for cigarettes is less price elastic among those who smoke for weight control. Thus, taxes on cigarettes will result in less behavior change (but more revenue collection and less deadweight loss) among those for whom the demand for cigarettes is a derived demand. Public health efforts to reduce smoking initiation and encourage cessation may wish to design campaigns to alter the derived nature of cigarette demand, especially among adolescent girls.
Keywords: I1; D01; H2; H3; Z18; 330; smoking; cigarettes; obesity; BMI; weight; derived demand; price elasticity; Rauchen; Körpergewicht; Jugendliche; USA